The Chinese vs Western Media Framing on Uygur Conflict - Kurniawan, Aucky Adi; Maulidya, Al Dina; Sa'ban, Khaerul; Indrawati, Indrawati (Journal of Islamic World and Politics, 2020)
This paper pays attention to the Uyghur conflict which became international news. A variety of reports about the Uygur appear with religious-based heroic narratives that corroborate discrimination, persecution, and all the miscience of the Chinese government against the Uyghur ethnic minority. As such, it aims to understand the difference in perspectives of the preaching of some Western mass media compared to the Chinese mass media in informing Uyghur related news. Compared to other ethnicity issues, the authors believed in certain interests behind the preaching of various online mass media to what was actually happening in Xinjiang. The author uses the framework of the framing theory of Pan Konciski and the constructivicist paradigm to interpret the news of the Uygur conflict.Â  The results of the study show Western media are more likely to have tendencies using words or sentences that drain the reader's emotions while Chinese media are more likely to be neutral in framing the news. It is a record for the authors that the public perception regarding the internationalization of issues occurring in a country can be influenced by how the media package news content.